Probiotic significance of Lactobacillus strains: a comprehensive review on health impacts, research gaps, and future prospects - Abdul Bari Shah; Aizhamal Baiseitova; Muhammad Zahoor; Ishaq Ahmad; Muhammad Ikram; Allah Bakhsh; Murad Ali Shah; Imdad Ali; Muhammad Idress; Riaz Ullah; Fahd A. Nasr; Mohammed Al-Zharani (Gut Microbes)
A rising corpus of research has shown the beneficial effects of probiotic Lactobacilli on human health, contributing to the growing popularity of these microorganisms in recent decades. The gastrointestinal and urinary tracts are home to these bacteria, which play a vital role in the microbial flora of both humans and animals. The Lactobacillus probiotic, i.e, Lactobacillus plantarum, Lactobacillus paracasei, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus crispatus, Lactobacillus gasseri, Lactobacillus reuteri, and Lactobacillus bulgaricus, are highly recognized for their remarkable probiotic qualities. The current study aims to highlight the beneficial effects of probiotics in different health conditions, point out the research gap, and highlight the future directives for the safe use of these probiotics in several health issues. Most importantly, we have added the most recent literature related to the characteristics and usage of these probiotics in clinical and pre-clinical settings. Based on the above statement, we believe that this is the first report on the application of probiotics in human diseases. By providing a deeper knowledge of the complex functions these probiotics play in both human and animal health, our analysis will direct future studies and developments in this rapidly developing field.